EFEKTIFITAS METODE EKSPERIMEN TERHADAP KEMAMPUAN MENGENAL WARNA DI KELAS A TK ABA TOBAYAN SLEMAN - Ika Maryani; Alfiani Defi Nofitasari (Pendidikan Guru PAUD, FKIP, Universitas Muhammadiyah Tasikmalaya, 2018)
The ability to recognize colors is very essential for underage children as it will trigger their sight and their brain. When children recognize colors, it will be automatically saved in their memory and thus it will influence their cognitive ability. Considering that fact, the researcher tries to use experimental method to help children recognizing colors. There for, this research aims to know the effectiveness of the experimental method in helping recognizing colors in A class of TK ABA Tobayan. This research belongs to experimental research with quasi design and pretest-posttest one group design. The researcher used verbal test and documentation as the main instrument to collect the data. The subjects of this research were seventeen students in A class of TK ABA Tobayan. The researcher analyzed the data using T test (Paired-sample t-Test) with significance rate 5%. The result showed that the value of t (38,276) > t table (df:16) (2,120) with p (0,000) < 0,05. From this result, it was know that Ha: accepted and Ho: rejected. Thus, the experimental method was proven effective to help children recognizing colors in A class of TK ABA Tobayan.